Electroacupuncture Ameliorates Depressive-Like Behaviors in Poststroke Rats via Activating the tPA/BDNF/TrkB Pathway - Dong H (Dove Medical Press, 2021)
Hao Dong,1,* Yan-Qiang Qin,2,* Ying-Chun Sun,2,* Hai-Jiang Yao,2 Xian-Kuan Cheng,2 Yan Yu,1 Shou-Si Lu1 1Beijing Bo’ai Hospital, China Rehabilitation Research Center, China Rehabilitation Science Institute, Beijing, People’s Republic of China; 2Treatment Center of TCM, Beijing Bo’ai Hospital, China Rehabilitation Research Center, China Rehabilitation Science Institute, School of Rehabilitation Medicine, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan-Qiang Qin; Ying-Chun SunTreatment Center of TCM, Beijing Bo’ai Hospital, China Rehabilitation Research Center, China Rehabilitation Science Institute, No. 10 Jiaomen North Road, Beijing, 100068, People’s Republic of ChinaTel +86 18612251241Email yanqiangqin@126.com; syccrrc@sina.comBackground: Electroacupuncture (EA) is a form of physical therapy that has been widely used in clinical practice in China. Post-stroke depression (PSD) is the most common neuropsychiatric complication after stroke. EA has been shown to have beneficial effects on PSD patients. However, the potential mechanism underlying the protective effects of EA on PSD remains unclear. Here, we investigated whether tissue plasminogen activator (tPA)/brain-derived neurotrophic factor (BDNF)/tyrosine kinase receptor B (TrkB) signaling pathway participates in the therapeutic effects of EA in a rat PSD model.Methods: Experimental PSD was induced by combining middle cerebral artery occlusion (MCAO) with chronic unpredictable mild stimulation (CUMS) in adult male rats. Bodyweight gain, neurological score, sucrose preference, and open field test were determined at 0, 7, 14, and 35 days after completing MCAO. The protein expressions of tPA, precursor BDNF (proBDNF), mature BDNF (mBDNF), and TrkB were measured by immunofluorescence and Western blot analysis. The tPA inhibitor plasminogen inhibitor-1 (PAI-1) was used to explore whether tPA plays a crucial role in the protective effects of EA on PSD.Results: Compared with the sham rats, the PSD rats showed decreased bodyweight, deteriorated neurological score, and significant depressive-like behaviors. EA remarkably reversed bodyweight loss, neurological deficit, and depressive-like behaviors in PSD rats. Immunofluorescence staining and Western blot analysis showed that PSD-induced decreased expression of tPA, mBDNF, and TrkB were prevented by EA. Furthermore, we found that the effects of EA against PSD-induced depressive-like behaviors were abolished by PAI-1, the specific inhibitor of tPA.Conclusion: Our results suggest that the improvement in depressive-like behaviors induced by EA is likely achieved via activation of the tPA/BDNF/TrkB pathway.Keywords: electroacupuncture, poststroke depression, depressive-like behaviors, tPA/BDNF/TrkB, chronic unpredictable mild stimulation